RSV infection in children hospitalised with severe lower respiratory tract infection at the Red Cross War Memorial Children's Hospital (2012-2013) - Morgan, Nicole (Department of Paediatrics and Child Health, 2024)
Objectives: Low- and middle-income countries carry the largest burden of Respiratory syncytial virus (RSV) disease, with most deaths occurring in these settings. This study aimed to investigate the burden of RSV disease in South African children hospitalised with lower respiratory tract infection (LRTI), with specific reference to incidence, risk factors, and co26 infections. Results: RSV was detected in 142 (30.9%; 95%CI 26.7-35.3) of the included 460 study children with LRTI. The median age of RSV-positive children was 4.6 (IQR 2.4-9.7) months compared to RSV-negative children of 10.5 (IQR 4.4-21.3) months, P = <0.001. Most cases occurred in autumn and winter with 126 (89%) cases over this period. IS demonstrated greater sensitivity for RSV diagnosis with 135 cases (95.1%) detected on IS and 57 cases (40.1%) identified on NP; P<0.001. The median length of hospital stay was 3.3 (SD 4.2) days in the RSV positive group and 2.7 (SD 3.3) days in the RSV negative group; P<0.001. The number of detected viral pathogens was a median of 1 (IQR 0-2) in RSV positive children (when RSV was excluded from the count) compared to 2 (IQR 2-3) in RSV negative children; P<0.001. The presence of RSV was independently associated with a reduction in the frequency of most viruses tested for on PCR. Conclusions: RSV is common in children hospitalised with LRTI and mainly affects younger children. There is an urgent need to find an effective vaccine to prevent RSV pneumonia in children worldwide, especially in LMICs that carry the greatest burden of disease.